Implementation of Character Education in Basic Social Sciences and Culture Subjects for State 106825 Primary School Students Using a Problem Solving Approach - Nasution, Maysarah; Putri Harahap, Nurindah Syahyanna (International Journal of Students Education, 2024)
By using a problem-solving -based approach , students tend to be more active because the learning atmosphere leads to students finding the results of their understanding through interaction, making it easier to understand teaching material, because it is assisted through concrete learning media. This research aims to describe teacher teaching activities, student learning activities and student learning outcomes at SD Negeri 106825 Batangkuis, Deli Serdang Regency through a problem-based approach model . This type of research is included in classroom action research (PTK). This research consists of two cycles consisting of 4 stages, namely planning (planning) , implementation (acting) , observation ( observing) , and reflection ( reflecting) . The subjects of this research were teachers and students of SDN 1 06825 Batangkuis for the 202 3 /202 4 academic year . The instruments used were observation and written test sheets. The data analysis technique uses averages and score categories. After carrying out the actions in this research, student learning outcomes experienced a significant increase from the initial completion results in cycle I, again increasing in cycle II. Student cognitive learning outcomes In cycle I, students who completed their studies had a completion percentage of only 6.3 , 4.0 % , while students who had not completed it were 35.50%. In cycle II, learning mastery increased to 8.50 %. The conclusion from the research results proves that the application of learning using a problem -based approach model can improve student learning outcomes in ISBD subjects SDN 10 6825 Batangkuis Deli Serdang Regency.